Cost-Utility Analyses in Foot & Ankle Surgery: A Systematic Review. Issue 3 (14th September 2018) - Karhade, Aditya; Kwon, John
Category: Other Introduction/Purpose: Orthopedic surgery lies at the forefront of the initiative to deliver value-based care. As a result, cost utility analyses have gained increased importance in the orthopedic literature. While other authors have previously reviewed the quality of US-based cost-utility analyses in orthopedic trauma, spine, sports, and arthroplasty, a similar analysis specific to foot and ankle surgery has not been performed. As such, the practicing foot and ankle surgeon does not yet have a comprehensive analysis of the available cost-utility analyses or the quality of the available evidence. The purpose of this study was to perform a systematic review of cost-utility analyses in foot and ankle surgery. Methods: A systematic review of foot and ankle studies was conducted to identify cost-utility based analyses published between 2000 and 2017. Of 687 studies screened by abstract, eight cost-utility foot and ankle studies were identified that met inclusion criteria and were scored by the Quality of Health Economic Studies instrument for overall quality. Results: Of the eight studies that met inclusion criteria, four were published in the U.S. Regarding topic, three examined end-stage arthritis, two examined diabetic foot ulcers, two examined ankle fractures and one examined ankle sprains. Cost-effective interventions identified by these studies included total ankle arthroplasty over ankle fusion or nonoperative treatment, adjunctive hyperbaric oxygen therapy for diabetic foot ulcers, suture button fixation over syndesmotic screws for unstable supination-external rotation type IV ankle fractures, and below knee cast and fracture boot immobilization over tubular bandages for acute severe ankle sprains respectively. The mean Quality of Health Economic Studies scores for these studies was 81.9 with interquartile range, 25th percentile score of 74.8 to 75th percentile score of 86. Conclusion: Despite the increasing focus on value-based care delivery, there are few foot and ankle cost-utility analyses in the current literature. Nonetheless, the quality of existing analyses is high as rated by the Quality of Health Economic Studies and certain interventions have been identified as cost-effective as highlighted above. The findings of this review can be used to help design future analyses in order to best demonstrate the cost-effectiveness of foot and ankle interventions.